2015
DOI: 10.1371/journal.pone.0129191
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Severe Pneumonia, Pneumococcal Pneumonia and Pneumonia Deaths in Indian States: Modelling Based Estimates

Abstract: The burden of severe pneumonia in terms of morbidity and mortality is unknown in India especially at sub-national level. In this context, we aimed to estimate the number of severe pneumonia episodes, pneumococcal pneumonia episodes and pneumonia deaths in children younger than 5 years in 2010. We adapted and parameterized a mathematical model based on the epidemiological concept of potential impact fraction developed CHERG for this analysis. The key parameters that determine the distribution of severe pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…There was also a marked difference in the death rates between the two centres in our studies. The variation in mortality in IPD by sites is not surprising and in agreement with other studies (22,30). In our case, the polarity observed between the two hospitals in both states were of varied socioeconomic status and health care accessibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was also a marked difference in the death rates between the two centres in our studies. The variation in mortality in IPD by sites is not surprising and in agreement with other studies (22,30). In our case, the polarity observed between the two hospitals in both states were of varied socioeconomic status and health care accessibility.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that undernourished children were more likely to present with severe pneumonia. Our ndings were supported by other published reports that malnutrition resulted in various nutritional de ciencies leading to severe infections including pneumonia (20)(21)(22). The increased predisposition of the nutrient-de cient host to infection is presumed to be largely due to impairment in the immune system (21,23).On the contrary, we found that obesity, especially among syndromic children, was associated with a fatal outcome in the disease.…”
Section: Discussionsupporting
confidence: 89%
“…( p < 0.05). Other studies have reported partial or lack of immunization as a significant risk factor for pneumonia [ 21 , 25 , 26 ]. This study also substantiated the higher risk of pneumonia among partially immunized children.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Manual measurement, although often the reference standard, can be imprecise and is affected by intraobserver variation as it requires focused concen tration In five studies, the incidence of WHO-defined severe pneumonia or severepneumonia with radiographic confirmation was approximately five episodes per 100 child-years in children below two years of age. 11,[33][34][35][36] The RESPIRE trial documented a relative risk of 0·67 for children with severe pneumonia in households with improved cookstoves, compared with those using traditional stoves. 10 Using this information, we can calculate the necessary sample size using a difference in two proportions (assuming pneumonia events are independent).…”
Section: Respiratory Ratementioning
confidence: 99%